2011
DOI: 10.1242/jeb.051631
|View full text |Cite
|
Sign up to set email alerts
|

A multilevel approach to examining cephalopod growth usingOctopus pallidusas a model

Abstract: SUMMARYMany aspects of octopus growth dynamics are poorly understood, particularly in relation to sub-adult or adult growth, muscle fibre dynamics and repro-somatic investment. The growth of 5month old Octopus pallidus cultured in the laboratory was investigated under three temperature regimes over a 12week period: seasonally increasing temperatures (14-18°C); seasonally decreasing temperatures (18-14°C); and a constant temperature mid-way between seasonal peaks (16°C). Differences in somatic growth at the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…The high values of Q 10 observed indicate that E. megalocyathus embryos showed a high sensitivity to temperature, just as it had been observed in the embryos of O. mimus , probably because the embryos have limited ability to regulate their basal metabolism. Clarke and Fraser (2004) suggested that basal metabolism is particularly sensitive to temperature due to the energy demands of ectotherms to maintain basic functions, while Semmens, Doubleday, Hoyle and Pecl (2011) highlighted the fact that octopuses respond to temperature changes abruptly.…”
Section: Discussionmentioning
confidence: 99%
“…The high values of Q 10 observed indicate that E. megalocyathus embryos showed a high sensitivity to temperature, just as it had been observed in the embryos of O. mimus , probably because the embryos have limited ability to regulate their basal metabolism. Clarke and Fraser (2004) suggested that basal metabolism is particularly sensitive to temperature due to the energy demands of ectotherms to maintain basic functions, while Semmens, Doubleday, Hoyle and Pecl (2011) highlighted the fact that octopuses respond to temperature changes abruptly.…”
Section: Discussionmentioning
confidence: 99%
“…In cephalopods, respiratory metabolism has a central role in the survival and physiological performance, due to the high demand of energy that those organisms have for growth (Petza et al, 2011;Semmens et al, 2011) and locomotion activity (Wells and Clark, 1996). Temperature is the main environmental factor that controls the respiratory metabolism in cephalopods; therefore, it is considered the most important factor controlling the energy turnover and the fitness of cephalopods (Mangold, 1983;Farías et al, 2009;Noyola et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…Where the total weight of females rose sharply reaching maximum sizes (4000 g) far exceeding those of the males (∼2500 g) for animals +1 year. Increased investment in reproductive development significantly contributed to this additional weight in mature individuals, as demonstrated by GSI, thus supporting the existence of two-phased growth (Mangold, 1983;Semmens et al, 2011). However, a potential limitation on the suitability of SIA for brooding females, is the preliminary observation by Leporati and Hart (2015) that females may cease forming stylet increments at the onset of spawning.…”
Section: Discussionmentioning
confidence: 63%